CORRELATION BETWEEN NEUTROPHIL-LYMPHOCYTE RATIO AND LIPID PROFILE IN TYPE-2 DIABETES MELLITUS - Nadwa Izza Azuma Arifin; Banundari Rachmawati; Meita Hendrianingtyas; Dwi Retnoningrum (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disease that can cause low-grade chronic inflammation related to insulin resistance. Recently, neutrophil to lymphocyte has become a potential marker of chronic inflammation. An abnormal lipid profile occurs due to lipotoxicity from insulin resistance. Objective: To prove the correlation between NLR and lipid profiles in T2DM patients. Methods: An analytic observational study used a cross-sectional approach to 45 medical records of T2DM patients who received treatment at Nasional Diponegoro Hospital Semarang. This study was conducted from October to November 2022. Data was collected by using consecutive sampling. Analysis of the correlation between NLR and lipid profiles used spearman’s correlation test. Results: The correlation between NLR and HDL cholesterol levels was p=0.035, r=-0.315. The correlation between NLR and cholesterol, LDL cholesterol, and triglyceride levels was p = 0.061, r = -0.281; p = 0.170, r = -0.208; p = 0.563, r = -0.089, respectively. Conclusion: There was a weak negative correlation between NLR and HDL cholesterol levels in T2DM patients, but there was no correlation between NLR and other lipid profiles.